Assessment of the toxicological risk from exposure to soils with lead and cadmium in the surroundings of the Infantas Industrial Park, Los Olivos - Olórtegui, Denisse (2020)
The objective of this study was to evaluate the toxicological risk due to exposure to soils with the presence of lead and cadmium in areas surrounding the Infantas Industrial Park in Los Olivos - Lima (2018). 40 soil samples were taken, 20 samples in the Carabayllo urbanization and 20 samples in the Villa del Norte urbanization. It was obtained that the concentration of Pb and Cd in Urb. Carabayllo had a mean of 66.97 mg / kg and 0.86 mg / kg; for Urb. Villa del Norte it is 51.43 mg / kg and 0.73 mg / kg respectively. The concentrations obtained comply with the Environmental Quality Standard (ECA) of the Ministry of the Environment of Peru. The Exposure Dose (DE) was estimated in the Carabayllo urbanization, for adults, a DEPb = 0.000143 mg / kg / day and DECd = 0.000002 mg / kg / day were obtained; and for children, a DEPb = 0.002494 mg / kg / day and DECd = 0.000032 mg / kg / day. In the Villa del Norte urbanization, for adults, a DEPb = 0.000109 mg / kg / day and DECd = 0.000002 mg / kg / day were obtained; and for children, a DEPb = 0.001916 mg / kg / day and DECd = 0.000027 mg / kg / day. After calculating the DE, we proceeded with the calculation of the Danger Index. An index below 1 (IP <1) was obtained, so the toxicological risk from exposure to the soil was acceptable for the population.